THE ROLE OF COGNITION AND MEMORY IN LEARNING AND TEACHING ENGLISH VOCABULARY - Mukhtarov, Mukhiddin (Журнал иностранных языков и лингвистики, 2023)
The study of foreign language especially in the early levels is accompanied by the close interaction of the native and foreign languages. This process is the zone of undivided attention of psycholinguists and methodologists. It is impossible to examine the second language personality partially from the student’s person in whole because we are speaking about the formation of the primary and secondary thesaurus.